Parathyroid hormone related protein and interleukin-6 mRNA expression in larynx and renal cell carcinomas from normocalcaemic and hypercalcaemic patients. Issue 10 (October 1995) - Schweitzer, D H; Boxman, I L; Löwik, C W; van Krieken, J H; Weissglas, M G; Baatenburg de Jong, R J; Papapoulos, S E
Abstract : AIMS–To determine the expression of parathyroid hormone related protein (PTHrP) and interleukin-6 (IL-6) mRNAs and their possible relation in malignant tumours, derived from patients with and without hypercalcaemia, commonly associated with humoral hypercalcaemia of malignancy. METHODS–PTHrP and IL-6 mRNA expression was studied by northern blot analysis in tumour specimens from 13 consecutive patients. Six patients (two with hypercalcaemia) had squamous cell carcinomas of the larynx and seven (one with hypercalcaemia) had renal cell carcinomas. RESULTS–There was no relation between the histological features of the tumours and the expression of either PTHrP or IL-6 mRNAs. PTHrP mRNA was detected in all squamous cell carcinomas, expression being highest in the two patients with hypercalcaemia. In the renal cell carcinomas PTHrP mRNA was expressed only in the patient with hypercalcaemia. IL-6 mRNA was detected in nearly all tumours studied but there was no apparent relation between its expression and that of PTHrP mRNA or serum calcium concentrations. CONCLUSIONS–PTHrP mRNA expression is increased in patients with hypercalcaemia but is not related to IL-6 mRNA expression. The results suggest a quantitative relation between PTHrP gene expression and hypercalcaemia, and imply that different mechanisms account for this expression in squamous and renal cell carcinomas.